Rotigotine transdermal patch in Parkinson's disease: a systematic review and meta-analysis. - Chang-Qing Zhou; Shan-Shan Li; Zhong-Mei Chen; Feng-Qun Li; Peng Lei; Guo-Guang Peng (PLoS ONE)
Background and methods The efficacy and safety of rotigotine transdermal patch in Parkinson's disease (PD) were studied in some clinical trials. We performed a systematic review and meta-analysis of randomized controlled trials to evaluate the efficacy, tolerability, and safety of rotigotine transdermal patch versus placebo in PD. Results Six randomized controlled trials (1789 patients) were included in this meta-analysis. As compared with placebo, the use of rotigotine resulted in greater improvements in Unified Parkinson's Disease Rating Scale activities of daily living score (weighted mean difference [WMD] -1.69, 95% confidence interval [CI] -2.18 to -1.19), motor score (WMD -3.86, 95% CI -4.86 to -2.86), and the activities of daily living and motor subtotal score (WMD -4.52, 95% CI -5.86 to -3.17). Rotigotine was associated with a significantly higher rate of withdrawals due to adverse events (relative risk [RR] 1.82, 95% CI 1.29-2.59), and higher rates of application site reactions (RR 2.92, 95% CI 2.29-3.72), vomiting (RR 5.18, 95% CI 2.25-11.93), and dyskinesia (RR 2.52, 95% CI 1.47-4.32) compared with placebo. No differences were found in the relative risks of headache, constipation, back pain, diarrhea, or serious adverse events. Conclusions Our meta-analysis showed that the use of rotigotine can reduce the symptoms of PD. However, rotigotine was also associated with a higher incidence of adverse events, especially application site reactions, compared with placebo.